High Genetic Similarity of MRSA ST88 Isolated From Pigs and Humans in Kogi State, Nigeria - Otalu, Otalu Jnr; Kwaga, Jacob K. P.; Okolocha, Emmanuel Chukuwdi; Islam, Md Zohorul; Moodley, Arshnee (Frontiers in Microbiology, 2018)
We determined the prevalence and genetic characteristics of methicillin-resistant Staphylococcus aureus (MRSA) isolated from pigs and humans between September 2013 and February 2015 in Kogi State, a central region in Nigeria. A total of 680 nasal swabs were collected and analyzed from pigs (n = 425) and “pig-contact” humans (n = 55) on 35 farms, and “non-pig-contact” humans (n = 200). MRSA was recovered from 20 (4.7%) pigs on 12 farms and 18 (7.0%) humans. Six (2.4%) of the human isolates were recovered from “pig-contact” humans, of which only three work on farms also harboring MRSA positive pigs. All 38 MRSA were resistant to β-lactams only, belonged to spa type t1603, sequence type (ST) 88, and mecA was associated with a SCCmec IVa element. Four isolates from a pig, a pig-contact human from the same farm, a pig-contact human from a pig farm in a different district, and a non-pig-contact human were subjected to whole genome sequencing (WGS). Core genome SNP analysis revealed high genetic similarity between strains (3–11 SNP differences), despite the temporal (2 year gap) and geographic (165 km) differences between isolates. Furthermore, these Nigerian isolates form a distinct clade when compared to other African MRSA ST88 isolates. All but one porcine strain was positive for scn suggesting a possible human origin and that pigs were either transiently contaminated by humans or result of a very recent human-to-pig transmission event. To our knowledge, this is the first report of genetically confirmed MRSA in pigs in Nigeria, which appear to be a typical CA-MRSA clone present in the human population.